How paediatric nurses frame the ethics of non-disclosure directives - El Ali, Mandy Mervat (Nursing ethics, 2025)
BackgroundNurses caring for hospitalised children can be told not to disclose information to the patient. Such non-disclosure directives in adult care pose recognised ethical problems, as they impinge on a patient’s autonomy and right to their own information, and have been discussed widely in the literature, from a physician’s perspective. Despite the ethical implications, there is less discussion of the ethics of withholding information from children. Nurses are well positioned to advocate for the rights of a child while considering their best interests; hence, nurses’ thinking about the ethics of non-disclosure directives is valuable.AimThe aim of this study was to explore the experiences and attitudes of nurses with truth-telling to seriously ill children, specifically how nurses frame and think about the ethical challenges when given a directive not to tell the truth to a child.DesignAn interpretive phenomenological approach was employed for this research, with data collected by semi-structured interviews.Participant PopulationTwenty-six nurses in Australia who had cared for children hospitalised with a serious illness in the previous 5 years.Ethical ConsiderationsEthics approval was granted by the University of Melbourne’s Human Research Ethics Committee (37283A). Informed consent was acquired from all participants.FindingsFour themes encompass the views nurse-participants expressed about the ethics of a non-disclosure directive: (i) Lying is wrong, (ii) Children should know, (iii) It’s hard for us when the child doesn’t know, but (iv) It’s not our place to tell. Nurse-participants described how a non-disclosure directive affected how they cared for their patients.ConclusionsNurse-participants believed they should be honest and articulated ethical reasons why children should be told the truth about their medical condition, but did not feel they were able to initiate this. It is recommended that nurses are supported in these ethically challenging situations and included in decision-making about how to respond when parents direct that information be withheld from their child.